Relative Prices and Economic Adjustment in the U.S. and the EU : A Real Story About European Monetary Union - Thomas, Alun.; Bayoumi, Tamim (Washington, D.C. : International Monetary Fund, 1994)
Structural vector autoregressions are used to analyze the relationship between real output and relative prices within the EU and the United States, Relative price variability appears to be more important for adjustment within the EU than the United States, reflecting the lower integration of goods and factor markets. In the absence of higher market integration, the lower relative price variability implied by the introduction of a single currency in the EU could well cause significant economic disruption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet